The Link Between Self-Dehumanization and Immoral Behavior. (August 2018) - Kouchaki, Maryam; Dobson, Kyle S. H.; Waytz, Adam; Kteily, Nour S.
People perceive morality to be distinctively human, with immorality representing a lack of full humanness. In eight experiments, we examined the link between immorality and self-dehumanization, testing both (a) the causal role of immoral behavior on self-dehumanization and (b) the causal role of self-dehumanization on immoral behavior. Studies 1a to 1d showed that people feel less human after behaving immorally and that these effects were not driven by having a negative experience but were unique to experiences of immorality (Study 1d). Studies 2a to 2c showed that self-dehumanization can lead to immoral and antisocial behavior. Study 3 highlighted how self-dehumanization can sometimes produce downward spirals of immorality, demonstrating initial unethical behavior leading to self-dehumanization, which in turn promotes continued dishonesty. These results demonstrate a clear relationship between self-dehumanization and unethical behavior, and they extend previous theorizing on dehumanization.